Influence of Mindset on Intellectual Performance - Muhammad Huzaifah Bin Adam; Siti Aisyah Binti Panatik (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
One of the priorities of education institutional existence is to empower student’s academic performance. Understanding their perception towards themselves and their mindset able to help students in their development. This study aims to identify the influence of mindset on intellectual performance. The population of this study sample covers 108 high school students ages 15 to 18 years old across Johor. The respondents of this research were selected through purposive sampling. In this research, student mindset had been measure using the growth mindset scale, and intellectual performance had been measured using 10 items of the psychometric and intellectual test. The data collected were analysed by using SPSS version 26. The results of this research showed that majority of the students has a growth mindset and majority of the students only able to achieve low intellectual performance level. In addition, the findings indicate that type of mindset did not influence intellectual performance.